2015
DOI: 10.1097/md.0000000000000726
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Spleen Diameter to Red Blood Cell Distribution Width

Abstract: Celiac disease (CD) is currently considerably underdiagnosed, setting the need for developing tools to select patients with probability of CD, who warrant further testing. Red blood cell distribution width (RDW) has been shown in previous studies to be a sensitive predictor for CD, but it lacks specificity. Splenic hypotrophy is also noted frequently in celiac patients.Our aim was to evaluate if spleen diameter to RDW ratio can be used as an indicator for CD.We evaluated 15 newly diagnosed CD patients, 52 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…In our cohort, significantly more patients in the newly diagnosed CD group had elevated RDW compared to the other two groups (79% vs. 37% and 17% respectively). Our findings are consistent with those of previous studies, which also reported high rates of elevated RDW in newly diagnosed CD patients (53.7% and 67% respectively) (9,11,24). RDW is known to be an early indicator of iron deficiency and altered erythropoiesis in CD patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our cohort, significantly more patients in the newly diagnosed CD group had elevated RDW compared to the other two groups (79% vs. 37% and 17% respectively). Our findings are consistent with those of previous studies, which also reported high rates of elevated RDW in newly diagnosed CD patients (53.7% and 67% respectively) (9,11,24). RDW is known to be an early indicator of iron deficiency and altered erythropoiesis in CD patients.…”
Section: Discussionsupporting
confidence: 83%
“…Among these hematologic indices, red blood cell distribution width (RDW) has been previously reported as a sensitive marker for CD (9,10), and its diagnostic performance as a screening test is improved in association with other markers (11). Low lymphocyte counts have also been described in association with celiac disease (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Balaban et al . [ 29 ] evaluated patients with inflammatory bowel diseases versus patients with irritable bowel syndrome and investigated the RDW differences between them. The results revealed that two-thirds of the celiac disease patients had elevated RDW levels, compared to 9% of the irritable bowel syndrome patients.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, RDW show important predictors in the evaluation of other disease that is aortic valve implantation as a poor prognostic marker, 17 use as an indicator in coeliac disease. 22 RDW may be useful in predicting the severity and functional outcomes of a stroke in acute stroke patients who have had symptoms for <24 hours, 21 and may also be a predictive tool in many other diseases, as is seen in RA patients who have one of the modifiable cardiovascular risk factors. 15 In a study by Peng et al .…”
Section: Discussionmentioning
confidence: 99%
“…An elevated RDW indicates a greater variability in the size of the circulating RBCs (anisocytosis) and can occur in patients with nutritional deficiencies, haemoglobinopathies, and haemolysis. 15 In addition, RDW is associated with cardiovascular disease, 15 - 20 acute cholecystitis, 14 acute stroke, 21 celiac disease, 22 ankylosing spondylitis (AS), 23 and mortality in patients with hip fractures treated with a partial prosthesis. 24 RDW as inflammation marker is associated with many diseases and chronic inflammation condition.…”
Section: Introductionmentioning
confidence: 99%